Arterial stiffness and atrial fibrillation: shared mechanisms, clinical implications and therapeutic options. Issue 9 (22nd September 2022) - Vio, Riccardo; Giordani, Andrea S.; Stefil, Maria; Madine, Jillian; Fairbairn, Timothy; Themistoclakis, Sakis; Salvi, Paolo; Caforio, Alida L.P.; Shantsila, Alena; Shantsila, Eduard; Akhtar, Riaz; Field, Mark; et al.
Abstract : Arterial stiffness (AS) and atrial fibrillation (AF) share commonalities in molecular and pathophysiological mechanisms and numerous studies have analyzed their reciprocal influence. The gold standard for AS diagnosis is represented by aortic pulse wave velocity, whose measurement can be affected by arrhythmias characterized by irregularities in heart rhythm, such as AF. Growing evidence show that patients with AS are at high risk of AF development. Moreover, the subset of AF patients with AS seems to be more symptomatic and rhythm control strategies are less effective in this population. Reducing AS through de-stiffening interventions may be beneficial for patients with AF and can be a new appealing target for the holistic approach of AF management. In this review, we discuss the association between AS and AF, with particular interest in shared mechanisms, clinical implications and therapeutic options.